The Pedagogies for critical agency: Portals to alternative futures - Ganas, Rieta; Behari-Leak, Kasturi; Chitanand, Nalini; Sabata, Siya (Critical Studies in Teaching and Learning, 2023)
‘Pedagogies in context’ are explored through a national project working with academic staff developers and new academics' induction and transitioning into higher education. Causal-layered analysis is used to explore the interplay between academic staff, institutional development, and contextual influences in shaping professional learning processes. Data generated by the project’s steering committee (SC) reflects on pedagogical encounters with the NATHEP participants and conference delegates (HELTASA, 2019). The outcomes of each intervention were compared by reflecting on who was in the room and how epistemological and ontological depth in each engagement was achieved. The study was guided by whether pedagogies are mobile and agile, irrespective of context. The SC asserts that pedagogies in context are relative to the participants, purpose and the project embedded in a specific context to achieve the epistemological, ontological, methodological, and axiological breadth and depth required. The portability of pedagogies from one context to another depends on aspects intrinsic to knowledge generation, transformation and decolonisation, engagement, being and becoming, and socio-cultural and historical conditions. This is also incumbent on the agility and flexibility of facilitators to adapt their repertoire to draw on a suite of contextually relevant pedagogical approaches.